Management of Educational Financing in Higher Education - Amrizal, Amrizal; Bahrun, Bahrun; Yusrizal, Yusrizal (LPPM Undiksha, 2021)
Education is one of the long-term investments that has the ultimate goal of producing reliable, and competitive human resources at both the local and global levels. Educational development will be difficult to achieve if it is not supported by adequate funding. This study aims to analyze the planning, implementation and supervision of education costs from the APBN and APBD. This study uses a descriptive method with a qualitative approach. Data collection techniques in the form of interviews, observation and documentation. The subject of this research is the Head of the Planning and Information System Administration Bureau, the Head of the Planning Section, the Head of the Finance Section, the Head of the Program Planning and Budgeting/SP4 Preparation System Team, the Head of the Information System Section and the Head of the Quality Assurance Agency. The results of the study indicate that planning uses a bottom up pattern with SP4 from the lowest work unit to the university level, the implementation of the budget is used to finance expenditures sourced from the APBN and APBD. Control is carried out as the implementation of the controlling function in the preparation of the Performance Accountability Report for Government Agencies to assess financial performance, the Quality Assurance Agency for performance achievements from the quality aspect. Meanwhile, the supervision is carried out by the BPKP, Bawasda and the Inspectorate General of the Ministry of National Education. Financing management is an evaluation in improving the quality of education.